A Sequential Algorithm for Solving a System of Nonlinear Equations (Journal of Computational Mathematics, 1991)
A sequential algorithm for solving a system of nonlinear equations based on the number-theoretic method is proposed. In order to illustrate the effectiveness of the method, the following two problems are discussed in detail: the problems for finding out a representative point of a continuous univariate distribution, and a fixed point of a continuous mapping of a closed bounded domain into itself.